Postthrombectomy Cerebral Hyperdensity: Usefulness as a Predictor of Future Hemorrhage or Infarction - Amgad Moussa; Ahmed El Serwi; Mohamed Tork (The Arab Journal of Interventional Radiology)
Aim: This study aims to examine the association between the presence of postinterventional cerebral hyperdensities (PCHD) and the occurrence of hemorrhagic transformation. Materials and Methods: We retrospectively analyzed the data of 33 patients who underwent successful mechanical thrombectomy for emergent large vessel occlusion of the anterior circulation and received two computed tomography (CT) scans of the brain; the first (CT1) within 4.5 h from the procedure and the second (CT2) within 4 days from the procedure. In patients who showed PCHD on CT1, CT2 was checked to detect hemorrhage or infarction in the location of the noted PCHD. Statistical analysis was done through the Fisher's exact test to detect the association between PCHD and hemorrhagic transformation. Results: 28 of the 33 patients (84.8%) showed PCHD on CT1. 20 of the 28 patients (71.4%) showed infarction on CT2, while 8 patients (28.6%) showed hemorrhage. The 5 patients that did not show PCHD on CT1 all showed infarction on CT2. Analysis of our results revealed that although cases with hemorrhage had more frequent positive contrast compared to infarction, this difference did not reach a statistically significant level (P = 0.302). Conclusion: We concluded that the presence of PCHD may be associated with future risk of hemorrhagic transformation, but this association did not reach statistical significance. Further studies are needed to validate these results, which may affect the use of antiplatelets in the immediate postthrombectomy period in the presence of PCHD.